O pensamento algébrico em livros didáticos da coleção A conquista da matemática dos anos finais do ensino fundamental: um olhar a partir da teoria antropológica do didático - ANDRADE, Belyt Sousa (2021)
ABSTRACT Difficulties in the teaching and learning process of Mathematics have been the object of attention among Basic Education teachers and researchers. Students' difficulties are constantly associated with the transition from arithmetic to algebraic concepts, the use of symbolic language and the focus on repetition of procedures. In this regard, we have noticed that the concept of learning based only on training and setting algebraic procedures no longer meets the current demands of school and society. Thus, it is essential that the student has access to mathematical knowledge in order to develop algebraic thinking. Therefore, the textbook stands out as a material full of didactic intentions that, in a way, drive the teaching and learning process of Mathematics in the classroom. Thus, in order to understand one of the faces of this phenomenon, throughout this investigation, we sought to answer the following question: how the collection of textbooks A Conquista da Matemática, approved by the PNLD, for thefinal years of elementary school, approached the algebraic thinking development process? Aiming to answer this question, we base this research on the foundations of Yves Chevallard's Anthropological Theory of Didactics, in order to understand the didactic and mathematical organizations in the textbooks of the collection. Data analysis allowed us to realize the concise and straightforward structure of the collection. Throughout its units, a conception more focused on an empiricist and constructivist approach can be noted. However, it does not fail to address situations related to problem solving and mathematical modeling. It is observed that the praxeologies are completed at the end of the last book in the collection, configuring paths for the development of algebraic thought.